Unemployment, parental distress and youth emotional well-being: The moderation roles of parent-youth relationship and financial deprivation - Frasquilho, Diana (2016)
We investigated, in a sample of 112 unemployed parents of adolescents aged 10-19 years, the links between parental distress and change in youth emotional problems related to parental unemployment, and the moderation roles of parent-youth relationship and financial deprivation. Data were analyzed using descriptive statistics and correlations. Further, simple moderation, additive moderation, and moderated moderation models of regression were performed to analyze the effects of parental distress, parent-youth relationship and financial deprivation in predicting change in youth emotional problems related to parental unemployment. Results show that parental distress moderated by parent-youth relationship predicted levels of change in youth emotional problems related to parental unemployment. This study provides evidence that during job loss, parental distress is linked to youth emotional well-being and that parent-youth relationships play an important moderation role. This raises the importance of further researching parental distress impacts on youth well-being, especially during periods of high unemployment rates.